MOBILITY, DISABILITY, AND SOCIAL ENGAGEMENT IN OLDER ADULTS - Rosso, Andrea L. (2013)
OBJECTIVE: To examine cross-sectional associations between mobility with or without disability and social engagement in a community-based sample of older adults METHODS: Social engagement of participants (n=676) was outside the home (participation in organizations and use of senior centers) and in home (talking by phone and use of internet). Logistic or proportional odds models evaluated the association between social engagement and position in the disablement process (no mobility limitations, mobility limitations/no disability, and mobility limitations/disability). RESULTS: Low mobility was associated with lower level of social engagement of all forms (OR=0.59, CI: 0.41–0.85 for organizations; OR=0.67, CI: 0.42–1.06 for senior center; OR=0.47, CI: 0.32–0.70 for phone; OR=0.38, CI: 0.23–0.65 for internet). For social engagement outside the home, odds of engagement were further reduced for individuals with disability. DISCUSSION: Low mobility is associated with low social engagement even in the absence of disability; associations with disability differed by type of social engagement.